NUMERICAL INVESTIGATION OF AN EXTERNALLY DRIVEN SPIN DYNAMICS IN SEARCH OF A CLASSICAL CONDENSATION OF WAVES - Yegovtsev, Nikolay (Nazarbayev University School of Science and Technology, 2017)
The following work is a numerical study of a recently discovered Bose-Einstein condensation of magnons at room temperature by purely classical means. The classical Hamiltonian of the system includes exchange and dipolar interaction as well as interaction with external magnetic field. The system under consideration is a 2-dimentional lattice of classical spins with fixed positions. Classical equations of motions are derived from this Hamiltonian by applying the Poisson-bracket formalism. Equations of motions were solved numerically by the 4th order Runge-Kutta algorithm and obtained spin dynamics is transformed to the frequency space by the means of Fourier transform. This spectral decomposition of the dynamics allows monitoring the occupation of the energy states and observing condensation into the lowest energy state. In this work, we were able to reproduce the dispersion curve with characteristic minimum at non-zero value of the wave-vector by varying parameters of the system. We discuss models for pumping and dissipation, and hope to implement them in the future work.
Keywords: numerical study; Hamiltonian; classical equations; Research Subject Categories::NATURAL SCIENCES::Physics